Flood Risk Assessment in Narainapur Rural Municipality using Analytical Hierarchy Process - Chaulagain, Rubi; Paudel, Rekha; Adhikari, Bijaya (Journal of Land Management and Geomatics Education, 2025)
Natural disasters are catastrophic events resulting from natural phenomena that cause significant damage to the environment, property, and human life. Narainapur Rural Municipality, located in Banke District of Lumbini Province, Nepal, is situated at approximately 27.4° N latitude and 91.6° E longitude. This municipality is characterized by its flat terrain and proximity to the Rapti River, which significantly influences its hydrology and flood dynamics. For the flood risk assessment using the Analytic Hierarchy Process (AHP), nine key factors were selected: curvature, soil type, distance to road, distance to stream, slope, rainfall, Topographic Wetness Index (TWI), Normalized Difference Vegetation Index (NDVI), and aspect. Each factor plays a significant role in flood susceptibility. AHP is a multi-criteria decision-making approach. The AHP is a decision support tool. It is used to solve complex decision problems uses a multi-level hierarchical structure of objectives, criteria, sub-criteria and alternatives. Hence, the Consistency Index (CI) for all parameters combined was found to be 0.063, indicating an acceptable level of consistency in the pairwise comparisons. The individual CI values for each parameter were as follows: slope (0.054), NDVI (0.038), soil type (0.070), distance to stream (0.030), rainfall (0.014), TWI (0.022), distance to road (0.015), aspect (0.029), and curvature (0.026). The approach proved effective in identifying areas vulnerable to flooding providing valuable insights for targeted disaster preparedness and management efforts.